Descriptive Analysis of the Direct Medical Costs of Multiple Sclerosis in 2004 Using Administrative Claims in a Large Nationwide Database - Prescott, Jeff D.; Factor, Saul; Pill, Michael; Levi, Gary W. (Journal of managed care pharmacy, 2007)
Multiple sclerosis (MS) is chronic and debilitating, afflicts patients in the prime of their lives, and requires costly, decades-long disease management. MS prevalence is increasing, and treatment with new drug therapies is expensive. The objectives of this analysis were to (1) determine the average total and component direct medical costs incurred in the treatment of MS patients in 2004, and (2) compare MS treatment costs and cost factors in 2004 with 1995. The data for this analysis were abstracted from the PharMetrics Integrated Patient-centric Database, which contains administrative claims data from more than 80 private and public health plans in the United States, representing more than 9.6 million unique patients in 2004. To be included in this analysis, each patient had to have at least 1 medical claim with a diagnosis of MS (International Classification of Diseases, Ninth Revision, Clinical Modification [ICD-9-CM] code 340) in the date of service period from January 1, 2004, through December 31, 2004. Patients were segmented according to patient age and sex, comorbid conditions, payer type, and use of specific types of disease-modifying drugs (DMDs). Episode Treatment Group (ETG) software (ETG numbers 149 or 150) was used to aggregate medical claims related to MS since not all MS-related medical claims have the ICD-9-CM code 340. ETGs are commonly used to aggregate administrative claims data and to define discrete periods of care (episodes); this study used ETGs only to aggregate administrative claims. Statistical comparisons were subsequently performed using analysis of variance and chi-square analyses. The source of the data for the aggregate MS treatment costs in 1995 was the Medstat MarketScan database. In calendar year 2004, a total of 13,420 patients were identified with a medical or hospital claim with ICD-9-CM code 340, a prevalence of approximately 14.0 per 10,000. The final study population was reduced to 10,099 patents (75.3%) after applying the criterion of 12 full months of available claims data. The total average annual cost for the 10,099 MS patients in 2004 was $12,879 (standard deviation, $18,582), 64.8% of which was attributable to the cost of prescription drugs and 61.4% to the cost of DMDs in particular, 26.2% to outpatient care, 7.8% to inpatient care, and 1.1% to emergency room visits. There was no difference in total average annual medical costs for males compared with females, but costs did differ among age categories and by insurance type and payer. A total of 5,810 patients (57.5% of the study population) reported at least 1 pharmacy claim for a DMD, and these patients had average annual costs of $18,944 compared with $4,662 total annual costs for MS patients who did not receive DMDs. Pharmacy costs represented 75.3% of annual medical costs for the patients who reported at least 1 pharmacy claim for a DMD but only 7.4% for patients who did not receive DMDs. A comparison of 2004 costs with 1995 costs (adjusted for 2004 based on the Consumer Price Index; CPI-U [All Urban Consumers, All Items]; 1982-84=100) demonstrated that total annual MS-related treatment costs increased by 35%, from $9,515 in 1995 to $12,879 in 2004. There was some difference in total annual MS-related treatment costs in 2004 among the 4 DMD therapy groups.$16,928 for glatiramer, $17,987 for IFN beta-1a (intramuscular), $19,616 for IFN beta-1b, and $22,557 for IFN beta-1a (subcutaneous), P <0.001. Pharmacy costs accounted for 65% of total MS-related medical costs in 2004 and 75% of total costs for the subset of MS patients(58%) who received at least 1 DMD.